A REVIEW ON CARBON SEQUESTRATION (NON-DESTRUCTIVE METHOD) IN URBAN ECOSYSTEM (International Association of Biologicals and Computational Digest, 2023)
Vegetation serves several critical functions in the biosphere, at all possible spatial scales. First, vegetation regulates the flow of numerous biogeochemical cycles, most critically those of water, carbon, and nitrogen; it is also of great importance in local and global energy balances. Such cycles are important not only for global patterns of vegetation but also for those of climate. The results of the vegetation study can be accompanied by other ecological parameters to assess the changes occurring in the local ecology The results may further be utilized to study the capability of the vegetation cover to mitigate the harmful effects of pollutionØ the results of the study may further be utilized to create a framework for planning and developing urban areas having higher carbon mitigating capabilities.Trees absorb Carbon dioxide from atmosphere and stored by photosynthesis, balancing the atmospheric Carbon dioxide in form of Carbon as Biomass. Rapid urbanization, Industrializing and imposes grand societal and environmental challenges such as compromised human health, alternation of local and emission by Using diverse types of land use pattern in increase the carbon sink of Forestry. The role of trees in the Forest In carbon cycles quite predictable (Singh & all, 2000) Regional climate, loss of natural habitats and biodiversity and degradation of water and Air quality. In recent decades, there has been much research accompanying quantifying the C sequestration of Urban Forests (Pataki et al., Zhao. Zhan et al. Accurate quantification of the Carbon storage in various in various urban forest is critical to improving our understanding of the role of urban green space in the urban carbon balance. Carbon sequestration estimation done by various methods like, Estimation of Tree volume, Above Ground Biomass, Below Ground Biomass, Total Biomass, Total Carbon Content, Determination of weight of Carbon dioxide sequestration in the Tree etc.
Keywords: Carbon stock, Carbon Sequestration, Non-Destructive methods. Urban Ecosystem